The Leadership Style of the Program Chair in Improving the Performance of Lectures and Its Relevance to the Quality of Education: A Case Study of the Informatics Engineering Program at ITB Swadharma - Waska Warta; Usanto Usanto; Adi Sopian; Nur Sucahyo (Universitas Muhammadiyah Enrekang, 2023)
This research examines the significance of effective leadership and job performance in achieving organizational or company goals. The research focuses on the leadership style adopted by the head of the information technology engineering study program in improving the performance of lecturers and its relevance to the quality of education in the program. This research holds important value in providing recommendations to decision-makers in educational quality improvement programs to face increasing competition in the higher education industry. This section highlights the importance of effective leadership and job performance in motivating and guiding employees to achieve organizational goals and their impact on the quality of education. Good leadership can involve various aspects, such as providing direction, implementing plans, and motivating organizational members to work effectively. The factors that support educational quality in the implementation model of Total Quality Management include: 1) leadership, 2) customer-focused approach, 3) organizational climate, 4) problem-solving teams, 5) meaningful data, 6) scientific methods and tools, and 7) education and training. The data sources used in this research include: 1) secondary data from internal and external evaluation reports, 2) questionnaires to measure the perceptions of students and lecturers, 3) interviews with the head of the study program, lecturers, students, and alumni, 4) policy documents and strategic plans, and 5) statistical data on the performance of lecturers and students.